EFL University Students’ Perceptions of TED Talks as Authentic Materials for Listening Comprehension: A Qualitative Descriptive Study - Najwa Laili Fathul Ulya; Girindra Putri Dewi Saraswati (Faculty of Education and Teacher Training of UIN Palopo, 2026)
This study aims to explore university students' perceptions of using TED Talks as a learning medium to improve their listening comprehension. Therefore, this study also investigates whether TED Talks are effective for students and whether TED Talks provide benefits or challenges for them. This study involved twenty undergraduate students in their third-year of the English Education Study Program at Universitas Negeri Semarang, with three students selected for interview. This research employed a descriptive method using a descriptive qualitative approach. The data in this study were collected through questionnaires and interviews. The findings show that students generally consider TED Talks useful and effective for their listening comprehension and vocabulary. Participants also reported that TED Talks motivated them to learn listening comprehension. However, several challenges emerged, including difficulty watching without subtitles and unfamiliar words. These challenges often hindered students' ability to understand the overall message, particularly for students with lower proficiency levels. The limitations of this study include the scope of the theory which only studies the listening comprehension area and limited approaches to listening learning to the use of TED Talks as a learning medium. In addition, this study was conducted with a limited yet focused participant group. Therefore, future researchers are suggested to expand the scope of relevant listening learning theories and include more participants to broaden the area of study.